Integrated electro-hydraulic machine with self-cooling possibilities for non-road mobile machinery - Ponomarev, Pavel (Strojniški vestnik, 2015)
Over the past few years, due to the introduction of Tier 4 emission legislations, new developments for non-road mobile machinery (NRMM) applications to meet these stringent targets have been introduced. This paper presents a design concept for self-cooling of integrated electro- hydraulic machinery for NRMM application. The applicability of this concept is shown for an integrated electro-hydraulic energy converter (IEHEC). Two cooling schematics (passive and active) are proposed. In the passive cooling scheme the coolant flow is obtained from the case drain leakage flow of the hydraulic machine. In the active cooling scheme a boost pump can be used for providing optimal coolant flow. We show that in an NRMM environment such an IEHEC can be utilized using a passive cooling scheme.
Keywords: efficiency; fluidna tehnika; hibridni prenosnik moči; hidravlična lekaža; hlajenje; izgube; necestna mobilna mehanizacija; rekuperacija energije; toplotni nadzor; učinkovitost